Intégration des TIC : types de connaissances abordées dans le discours d’enseignants en exercice et d’étudiants en formation initiale - Lefebvre, Sonia (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
This case study examines knowledge activated in in-service and preservice teachers discourse in relation to the implementation of ITCs for pedagogical purposes. Analysis based on the Technological Pedagogical and Content Knowledge (TPACK) model (Koehler & Mishra, 2008) indicates that both in-service and pre-service teachers activate primarily technological and pedagogical knowledge, and little disciplinary knowledge. Further research should focus on the development and analysis of TPACK-derived instruments for initial and continuing training.